2012
DOI: 10.1159/000334664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serum Lipid Levels on Stroke Outcome after rt-PA Therapy: SAMURAI rt-PA Registry

Abstract: Background: The effects of lipid levels on clinical outcomes after ischemic stroke are controversial. Whether admission lipid levels and prior statin use are associated with early intracerebral hemorrhage (ICH) and long-term functional outcome after recombinant tissue plasminogen activator (rt-PA) therapy for stroke patients was investigated. Methods: Ischemic stroke patients who received intravenous rt-PA from a multicenter registry were studied. Lipid levels on admission, including total cholesterol, high-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 85 publications
3
26
0
Order By: Relevance
“…In mouse models of stroke, HDL infusion and S1P 1 receptor activators can reduce neuronal I/R injury in animal models and in human clinical trials (8, 10, 42, 43, 47, 49, 50). Thus, ApoM-Fc–S1P may provide a novel strategy for treatment of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse models of stroke, HDL infusion and S1P 1 receptor activators can reduce neuronal I/R injury in animal models and in human clinical trials (8, 10, 42, 43, 47, 49, 50). Thus, ApoM-Fc–S1P may provide a novel strategy for treatment of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…To determine dose-response relationships, a similar experiment was performed using PBS (vehicle control) or 30 µg (1.3 mg/kg) of either ApoM-Fc or ApoM-Fc–TM suspended in PBS. In addition, the S1P 1 antagonist W146 (10 mg/kg) (8) was used in similar experiments. W146 was administered by intraperitoneal injection at time 0 and then at 24-hour intervals (24 to 96 hours and then again at 168 hours).…”
Section: Methodsmentioning
confidence: 99%
“…40 Recently, among 489 patients with acute IS treated with tPA within 3 hours of stroke onset, high HDL-C levels were significantly associated with a good outcome at 3 months. 41 This suggests that HDL supplementation may be beneficial at the acute stage of stroke. Raising HDL levels encompasses 2 different strategies: HDL infusion and HDL-raising drugs.…”
Section: Effects Of Combined Treatment On Bbb Integrity In Vivomentioning
confidence: 99%
“…HDL cholesterol also has a potential to improve fibrinolytic activity derived from vascular endothelial cell [33]. We previously reported that the admission HDL cholesterol level was associated with favorable outcome 3 months after intravenous rt-PA therapy [34]. HDL cholesterol may play an important role to improve thrombolysis in patients treated with rt-PA.…”
Section: Discussionmentioning
confidence: 99%